(untitled) - Miller, Rex (New York, 2008)
Turn to Industrial Electricity and Electric Motor Controls for complete coverage of the entire industrial electrical field_from the basics of electricity to equipment, to troubleshooting and repair
Keywords: Electric machinery,Industrial electronics,Electric motors,Cơ học điện tử,Điện công nghiệp; Electronic control